The Strategy of Developing Agricultural Supply Chain in Terms of Food Security in Ukraine - O. Varchenko; I. Svynous; Y. Grynchuk; K. Tkachenko; O. Shust (International Journal of Supply Chain Management, 2018)
Abstract- The calculation of the forecasted commodity supply in terms of the main types of food in Ukraine is carried out in three variants. The normative demand for investing resources in the production of livestock products is developed on the basis of the determination of the requirements for demand in the basic, human and working capital. The necessary volume of investment production of the main types of agricultural supply chain products for the satisfaction of the country's needs in achieving food security of the country is determined. It was established that the provision of scientifically grounded needs of the population in food products requires the achievement of a balanced resource supply of the agricultural supply chain and its rational use and increasing the purchasing power of the population of the country. The regulatory requirement for investment capital for the production of livestock products has been determined with the aim of achieving a balance of resource support for production through the introduction of innovative resource-saving technologies and the modernization of industries, as well as in the development of targeted regional programs for the development of the agricultural supply chain. Keywords- resource, consumption, food security, agricultural supply chain, Ukraine.